CORPORATE STANDARD OF ICT COMPETENCE OF MASTERS - N. Morze; O. Buinytska (Kherson State University, 2014)
Current labor market demand determines the modification of the system of higher education, including the transfer of emphasis on the educational process in its final qualitative result, a paradigm shift from knowledge education to competency. Student should must possess ICT competence that today has become a part of professional competence of professionals of any type. The purpose of the study is to develop standards in the ICT competence of all members of the educational process to ensure the quality of university education and the creation and subsequent implementation of educational policies of the University. The paper highlights the need to develop a corporate standard of ICT competence of masters based on UNESCO scientific approaches. It describes model, the level of ICT competence and tools for monitoring its formation in the future for today's professionals. For each of the selected three levels of ICT competence (basic, advanced and professional) determined necessary knowledge and skills, talents and ideas to master. The necessary and sufficient conditions are determined for the formation of the ICT competence of masters in modern university, proffered examples of tasks and competency requirements for the personal educational electronic space for student and educational electronic space of university. Developed and approved corporate standard provides appropriate expertise contemporary specialist who meets the requirements of the labor market and will allow the graduate to be successful in today's information society.